Detector de ionização de descarga de barreira dielétrica (BID): uma abordagem comparativa para determinação de pesticidas e outros compostos por GC - Lopes, Amanda Fonseca (2021)
The Dielectric Barrier Discharge Ionization Detector (BID) is one of the latest detectors used in gas chromatography (GC). It outperforms well-established detectors such as the TCD, FID and MS in some situations. The first mapping of the main applications of the BID was described in the present work and indicated the lack of studies with polycyclic aromatic hydrocarbons (PAHs), organophosphorus (OPPs) and organochlorine (OCPs) pesticides. In addition, several advantages of the BID over classical detectors such as FID and TCD, mainly for the determination of gaseous compounds. An unprecedented comparative study between BID and FID for the determination of 30 compounds (PAHs, OPPs, OCPs and aliphatic hydrocarbons (HAs)) was also carried out, in an attempt to contribute to a better understanding of the potential of the GC-BID. Ionization energy (EI) and HOMO orbital energy (EHOMO) data obtained by density functional theory (DFT) were used for comparative purposes. The study revealed superior responses generated by the BID system in all situations, indicated the independence of the BID response with molecular mass and that this response is little affected by heteroatoms and electrophilic substituents, compared to FID. The highest responses obtained in the BID for PAHs, OPPs, OCPs and HAs could also be explained by the lower EI values obtained for all molecules under the conditions of the BID. The EI was the parameter that may have most influenced the responses of the two detectors studied, especially for the BID. The HAs showed better correspondence between these parameters and the responses. It is possible that other conditions, such as the presence of more efficient signal collectors and amplifiers than those contained in the FID system, may influence the BID response. This work also explored the development of the first method using the GC-BID for the determination of eleven OPPs and OCPs pesticides in vegetables (lettuce, tomato and pepper). The evaluation of figures of merit for OPPs and OCPs indicated good selectivity, wide linear range, and acceptable LD and LQ values in various situations. The method was exact and precise, particularly at higher levels of fortification. The matrix effect (EM) was present at all points of the curves, mainly at lower concentrations and large values were found for methamidophos. Positive and negative EM were more frequent in bell pepper and lettuce, respectively. A study with real samples of lettuce, tomato and pepper collected at five different points in Fortaleza indicated the presence of peaks with the same retention time as ethoprophos, α-endosulfan and profenofos in some samples of lettuce and tomato. This evidences the feasibility of the BID for the determination of pesticides in these matrices. The studies carried out here provided a better understanding of the factors associated with the power of response of the BID and indicate that it can be an interesting for chromatographic analyzes aimed not only at the determination of gaseous compounds, but also for others, such as OPPs and OCPs which until then had not been explored with the BID.